PENGARUH EFIKASI DIRI TERHADAP KINERJA GURU DI SMA PGRI 3 JAKARTA - Achmad Sjamsuri; Nani Muliyani (Faktor Jurnal Ilmiah Kependidikan, 2019)
This study is aimed at exploring the influence of self-efficacy on teacher’s performance in conducting this research, the researcher employed survey method using path analysis. The research sampling method applied was simple random sampling. Based on the result oh theis study, it was found that positif self-efficacy had direct effect on teachers performance. There efore, from the findings it is concluded that self-efficacy, are important factors the influence the effecveness of high school teachers performance in’’SMA PGRI 3 Jakarta’’.